Public Health Nurse-delivered Group Cognitive Behavioural Therapy for Postpartum Depression: A Randomized Controlled Trial. (June 2022) - Van Lieshout, Ryan J.; Layton, Haley; Savoy, Calan D.; Haber, Erika; Feller, Andrea; Biscaro, Anne; Bieling, Peter J.; Ferro, Mark A.
Objectives: To examine the effectiveness of group cognitive behavioural therapy (CBT) for postpartum depression (PPD) delivered by public health nurses with little to no previous psychiatric training at improving depression, worry, social support and the mother-infant relationship. Methods: Mothers (n = 141) living in Ontario, Canada with Edinburgh Postnatal Depression Scale Scores ≥10 and an infant <12 months of age were randomized to receive nine weekly 2-h sessions of in-person group CBT for PPD delivered by two public health nurses plus treatment as usual (TAU; experimental group) or TAU alone (control group). Primary outcomes were change in EPDS score and current major depressive disorder (Mini International Neuropsychiatric Interview) assessed immediately post-treatment (T2). Secondary outcomes included maternal worry, social support, and quality of the mother-infant relationship. All outcomes were assessed again six months post-treatment (T3). Results: Participants in the experimental group had statistically significantly greater reductions in PPD symptoms immediately post-treatment (T2) (B = -5.35, p < 0.01), were more likely to manifest a clinically significant improvement in EPDS scores (≥4 points; OR = 3.44, 95%CI: 1.49–7.94), and no longer have symptoms consistent with current MDD (OR = 5.31, 95% CI: 1.78–15.83). Six months post-treatment (T3), experimental group participants had higher odds of clinically significant PPD improvement (OR = 5.10, 95%CI: 1.89–13.78), while 25% of the experimental group and 70% of remaining control group participants reported current MDD ( p < 0.01). Statistically significant improvements in worry and the mother-infant relationship were also observed, decreases maintained at six months post-treatment. Conclusions: Public health nurses with little to no previous psychiatric training can be trained to deliver effective group CBT for PPD to improve depression, worry, and the mother-infant relationship. Task shifting PPD treatment with group CBT to public health nurses could improve treatment uptake and lead to better outcomes for mothers, families, and the healthcare system. (Trial Registration NCT03039530)